GSK-3beta Inhibitor Induces Expression of Nrf2/TrxR2 Signaling Pathway to Protect against Renal Ischemia/Reperfusion Injury in Diabetic Rats - Bo Hu; Yuhong Wu; Jie Liu; Xiaohua Shen; Fei Tong; Guangtao Xu; Ruilin Shen (Karger Publishers, 2016)
Background/Aims: Diabetes mellitus (DM) can lead to renal damage and dysfunction, and exacerbate renal ischemia/reperfusion injury (RI/RI). The aim of this study was to investigate the protective effect of GSK-3β inhibitor TDZD-8 against RI/RI through Nrf2/TrxR2 signaling pathway in a rat DM model. Methods: A DM rat model was established by a single injection of streptozocin. Diabetic rats were pretreated with TDZD-8 (1 mg/kg bw) or TDZD-8+auranofin (10 nmol/L, 5ml/kg bw), and then subjected to 45-min ischemia and 24-h reperfusion. Rats were equally randomized into four groups: a Sham-operated group, a RI/RI group, a TDZD-8 group, and a TDZD-8+auranofin group. Serum levels of BUN and Scr were measured. SOD activity, MDA content, and Nrf2, TrxR2 and caspase-3 expressions in rat kidney tissues were determined. Results: Renal function was improved, oxidative stress and cell apoptosis were reduced, and the expression of Nrf2 and TrxR2 was up-regulated in TDZD-8 treated rats as compared with those in auranofin treated rats. Conclusion: TDZD-8 may exert its protective effect against RI/RI by regulating the Nrf2/TrxR2 signaling pathway in the kidney tissue in DM.